RETRACTED ARTICLE: Sequential Casting Using Multiple Materials: A Bronze Age "Royal Sceptre" from the Halil Rud Valley (Kerman, Iran). Issue 1 (2nd January 2021) - Unknown
Abstract : Retraction: Sequential Casting Using Multiple Materials: A Bronze Age "Royal Sceptre" from the Halil Rud Valley (Kerman, Iran) We, the Editor[s] and Publisher of Iran, have retracted the following article: Nasir Eskandari, Francois Desset, Lara Maritan, Arnaldo Cherubini, & Massimo Vidale, Sequential Casting Using Multiple Materials: A Bronze Age "Royal Sceptre" from the Halil Rud Valley (Kerman, Iran), Iran (2019), doi: 10.1080/05786967.2019.1605494 Please note that this article has been removed from Iran as it is a Duplicate Publication of: Nasir Eskandari, Francois Desset, Lara Maritan, Arnaldo Cherubini, & Massimo Vidale, Sequential Casting Using Multiple Materials: A Bronze Age "Royal Sceptre" from the Halil Rud Valley (Kerman, Iran), Iran (2019), doi: 10.1080/05786967.2019.1607162 We have been informed in our decision-making by our policy on publishing ethics and integrity and the COPE guidelines on retractions. The retracted article will remain online to maintain the scholarly record, but it will be digitally watermarked on each page as "Retracted".